2023
DOI: 10.7759/cureus.39619
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: An Instagram Analysis

Umme Aiman,
Maneeth Mylavarapu,
Namra V Gohil
et al.

Abstract: Introduction Although the pathophysiology of obesity is widely recognized, its psychological and social aspects have received more attention in treatment and prevention. Social media technological advancements offer a quicker, more accessible, and broader platform for the dissemination of information. Hence, social media may significantly impact eating habits and body image development in children and adolescents, potentially turning into a risk factor for obesity if the behaviors being pushed are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
2
1
1
Order By: Relevance
“…A staggering amount of posts -70.4% of posts (138 posts) -were posted by patients. This is in contrast to a study by Aiman et al, 2023, which shows 54.52% of posts (229 posts) on obesity were posted by the health and wellness industry/website, and only 13.81% of the posts (58 posts) were posted by the survivors or the patients [10]. This suggests that individuals with bipolar disorder or other mental illnesses are more engaging on social media platforms compared to other nonpsychiatric illnesses like obesity, stroke, and diabetes.…”
Section: Discussioncontrasting
confidence: 86%
“…A staggering amount of posts -70.4% of posts (138 posts) -were posted by patients. This is in contrast to a study by Aiman et al, 2023, which shows 54.52% of posts (229 posts) on obesity were posted by the health and wellness industry/website, and only 13.81% of the posts (58 posts) were posted by the survivors or the patients [10]. This suggests that individuals with bipolar disorder or other mental illnesses are more engaging on social media platforms compared to other nonpsychiatric illnesses like obesity, stroke, and diabetes.…”
Section: Discussioncontrasting
confidence: 86%
“…In our survey, 28.24% of the posts were about prevention, which is comparable to the study on obesity conducted by Aiman et al, where 25% of posts were about preventing obesity, indicating that fewer videos communicate preventative messages [10]. In order to spread concise messages to specific audiences, public health authorities may utilize social media platforms as an effective method to raise public health awareness.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, doctors' contributions had a considerably higher GQS score than posts from healthcare organizations and other groups, which shares a similar observation in a study done by Rudisill et al on YouTube as a source of information on pediatric scoliosis: a reliability and educational quality analysis, where JAMA scores for videos uploaded by patients were considerably lower (p = 0.004) [15]. On the other hand, videos uploaded by academics or doctors had higher perceived stress scale (PSS) scores (p = 0.003) and showed a tendency toward better GQS score (p = 0.051) also in keeping in line with a related Instagram analysis research by Aiman et al, which revealed doctors had a large percentage of accurate postings [10].…”
Section: Limitationssupporting
confidence: 80%
“…Complementary trends were also found on other social media and web-based platforms. A study by Aiman et al, which focused on evaluating the quality and reliability of the content on obesity on Instagram, reported that the posts by doctors and healthcare organizations on obesity had the highest quality and reliability scores [12].…”
Section: Discussionmentioning
confidence: 99%